Stress response and changes in amino acid requirements in Senegalese sole (Solea senegalensis Kaup 1858) - Aragão, C. (2014)
Fish in aquaculture are often exposed to various stressors that may change their ability to survive or limit growth. Amino acids are used for processes other than growth, including stress response. This study intended to analyse how repeated acute handling stress can affect growth and amino acid requirements in fish. Senegalese sole juveniles were weekly held in the air during 3min (Handling) for 9 weeks; Control groups were left undisturbed. Growth and plasma levels of stress indicators and of free amino acids were assessed at the end of the experiment. Plasma cortisol and osmolality levels showed that fish in the Handling treatment were stressed, but growth was unaffected. Plasma amino acid concentrations indicate that their requirements in stressed fish were altered, which probably reflects the synthesis of proteins or other specific compounds related to stress response.